The Effect Of Perceptions Of Ease Of Use And Perceptions Of Risk On Impulse Buying Through Shopping Interest As A Mediating Variable Among Shopeepay Users In The Cirebon Region - Sekar Ayu Hutami; Yusuf Yusuf (Eduvest - Journal of Universal Studies, 2026)
Objectives: This study aims to 1) To analyze and determine the effect of Perception of Ease of Use on Shopping Interest, 2) To analyze and determine the influence of Risk Perception on Shopping Interest, 3) To analyze and determine the influence of Shopping Interest on Impulse Purchases, 4) To analyze and determine the influence of Perception of Ease of Use on Impulse Purchases, 5) To analyze and know the influence of Risk Perception on Impulse Purchases. Method: This study is a quantitative research that uses a causal-explanatory approach to test and explain the cause-and-effect relationship between independent, mediating, and dependent variables through testing statistical hypotheses. The research sample was 170 respondents with a data collection method through google form. The data was analyzed using SMART PLS version 4. Results: These results show that the higher the user's interest in shopping, the greater their tendency to make impulsive purchases without prior planning. Shopping interest has been proven to mediate the influence of the perception of ease of use on impulse purchases. This means that the ease of use of ShopeePay does not directly encourage impulse purchases, but first increases shopping interest which then triggers impulse buying behavior. Shopping interest has also been shown to mediate the influence of risk perception on impulse purchases. Low risk perception increases users' shopping interest, which ultimately encourages impulse purchases. Thus, shopping interest plays an important mediating variable in explaining the impulse purchase behavior of ShopeePay users.